Neck Circumference as a Valuable Tool to Identify the Risk of Metabolic Syndrome in Mexican Children - Evelyn Valencia-Sosa; Guillermo Julián González-Pérez; Clío Chávez-Palencia; María Guadalupe Vega-López; Enrique Romero-Velarde (MDPI AG, 2024)
Background/Objectives: Neck circumference (NC) has been proposed as a simple measurement to identify patients with overweight and obesity. It has been found that adipose tissue at the cervical level is associated with the presence of metabolic alterations. The aim of this study was to estimate the association between NC and indicators of Metabolic Syndrome (MS) to subsequently estimate its capacity to identify the risk of MS compared to waist circumference (WC) and Body Mass Index (BMI). Methods: A cross-sectional study was carried out with a sample of 286 children 6-9 years old who attended six public primary schools in Jalisco, Mexico. Pearson's correlation coefficients along with sensitivity and specificity tests were performed to analyze the relationship between NC and MS indicators. Odds ratio (OR) and concordance analyses were performed considering the Kappa index. Results: NC showed statistically significant correlations with all MS indicators except for LDL cholesterol and total cholesterol. The cut-off points of NC to identify MS according to sex was >27.4 cm for girls and >29.8 cm for boys. The association of NC with values above the cutoff point and the presence of MS was OR: 21.6 (CI: 7.11-65.74). Conclusions: NC represents a simple and cost-effective alternative to identify children at risk of MS when compared to BMI and WC.